Are patients bypassing paediatric cardiology outreach clinics?. (25th January 2017) - Fletcher, Alexander; Samson, Ray; McLeod, Karen
Abstract: Previous studies have identified that receiving specialist care close to home can positively influence patients' experience. Despite this, a review of cardiology outpatient appointments at the Royal Hospital for Children in Glasgow demonstrated that a large number of families are bypassing their local children's cardiology centre to attend cardiac clinics at the specialist children's surgical centre. We used patient questionnaire, audit of local facilities, and examined the relationship between diagnosis and bypass numbers to better understand factors influencing this trend. Our results suggest that patient preference, short travelling distance to specialist children's cardiac centre, a more severe cardiac diagnosis, and inconsistent local facilities, expertise, and support are likely to influence a family's decision to bypass their local children's cardiology centre.